First record of the invasive Lagria villosa (Fabricius, 1781) (Coleoptera: Tenebrionidae: Lagriinae) in Europe - Ruzzier, Enrico; Martínez-Muñoz, Carlos A. (Zootaxa, 2021)
The lagriid beetle Lagria villosa (Fabricius, 1781), an invasive species of African origin, is recorded for the first time in Europe. A single specimen was found in November 2020 in Turku (Finland) inside a box of table grapes from a local supermarket. This species, included in the EPPO Global Database and in the CABI Invasive Species Compendium, is widely recognized as a significant pest of crops.